2020
DOI: 10.3390/ani10112041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inclusion of Degraded and Non-Degraded Date Pits in Broilers’ Diet on their Intestinal Microbiota and Growth Performance

Abstract: The current study aims to assess the effect of non-degraded date pits (NDDP) and degraded date pits (DDP) in broilers’ diets on gut microbiota and growth performance. The degradation of date pits (DP) occurred via the cellulolytic fungus Trichoderma reesei by a solid-state degradation procedure. One-day-old Brazilian broilers were allocated into six dietary groups: (1) maize–soy diet, (2) maize–soy diet with oxytetracycline (20%, 50 g 100 kg−1), (3) maize–soy diet with 5% NDDP, (4) maize–soy diet with 10% NDDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Date pits are a rich source of fibers, with fiber content varying between 60 and 80 g/100 g total weight (Habib and Ibrahim, 2009;Ataye et al, 2011;Habib et al, 2017;Metoui et al, 2019;Alyileili et al, 2020a;Al-Khalili et al, 2021). As lignocellulosic biomaterial, the insoluble fiber content consists of cellulose, hemicellulose, and lignin, .…”
Section: Dietary Fibersmentioning
confidence: 99%
“…Date pits are a rich source of fibers, with fiber content varying between 60 and 80 g/100 g total weight (Habib and Ibrahim, 2009;Ataye et al, 2011;Habib et al, 2017;Metoui et al, 2019;Alyileili et al, 2020a;Al-Khalili et al, 2021). As lignocellulosic biomaterial, the insoluble fiber content consists of cellulose, hemicellulose, and lignin, .…”
Section: Dietary Fibersmentioning
confidence: 99%
“…Recently, there have been trends to utilize the phytochemical properties of industrial fruit or herbs wastes in animal feeding, which will not only reduce environmental burdens, but also improve animal production and health [ 47 , 48 ]. Similarly, phytochemical or nutraceutical prosperities of date pit or waste have been explored or attempts have been made to improve them using solid state degradation by Trichoderma reesei L. and their utilization in animal feeds [ 49 , 50 , 51 , 52 , 53 ]. Alyileili et al [ 49 ] reported that solid state degradation of date pit with T. reesei enhanced mannan oligosaccharide content, phenolic (142 g gallic equivalent/kg) and flavonoid (117 g rutin equivalent/kg) content of degraded date pits and antioxidant activities.…”
Section: Recent Knowledge and Future Directionmentioning
confidence: 99%
“…However, body weight, feed intake, and feed conversion ratio were not influenced by 10% degraded date pits compared with the control [ 52 ]. Alyileili et al [ 53 ] compared 5 and 10% non-degraded date pits vs. degraded date pits in chickens. The populations of Escherichia coli, Salmonella , Campylobacter and Shigella spp.…”
Section: Recent Knowledge and Future Directionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding date pits meal, it could be fed to laying hens up to 5% without adverse effects on their performance and egg quality. In addition, broilers fed diet incorporated with 4% date pits meal showed an ability to resist the deleterious effects of aflatoxine B1 [14].…”
Section: Date Wastesmentioning
confidence: 99%